Determining the right location for Turkey’s nuclear energy investment projects based on zero-carbon emission purposes - Çağlayan, Çağatay; Kararoğlu, Dilan; Yavuz, Duygu (Springer Science and Business Media Deutschland GmbH, 2022)
Turkey’s energy needs are increasing in parallel with the increasing industrialization and population. To meet its increasing energy needs, Turkey needs energy sources that are more sustainable and in line with zero-carbon emission targets. Although fossil fuels can meet the energy needs, they are not energy sources suitable for Turkey’s targets. Because there are not enough fossil fuel reserves in Turkey, fossil fuels are not sustainable and fossil fuels cause high carbon emissions. Therefore, renewable energies and nuclear energy come to the fore. Turkey continues to invest in renewable energy, but renewable energy investments in the country will not be sufficient to meet the anticipated energy demand in the future. Thus, the best alternative option for Turkey is nuclear power plants. The main purpose of Turkey’s nuclear power plant projects is to protect energy resources, ensure energy security, reduce environmental pollution, and reduce the total cost of all electricity generation, but deciding for a nuclear power plant site is a very strategic and complex process. In this study, criteria for determining the right location in Turkey’s nuclear energy investment projects were determined and the relevant literature was examined. The seismic activity and population density of the region where the power plant will be established should be low, and the availability and sufficiency of cooling water in the said region should be high. Appropriate topography of the region will increase the safety of the reactor to be established and environmental sensitivity will protect the biodiversity and natural resources of the region. In addition, the power plant area should be built away from airports and areas of high terrorist activity to prevent aircraft crashes and terrorist attacks. Finally, cost is an important criterion for nuclear power plant projects. A cost-oriented approach to site selection will increase the efficiency of these projects.
Keywords: Energy Investments; Location Selection; Nuclear Energy Projects; Zero-Carbon